2008
DOI: 10.1007/s00127-008-0317-1
|View full text |Cite
|
Sign up to set email alerts
|

Rural−urban differences in Austrian suicides

Abstract: In line with recent findings from other western countries, we showed a growing gap between rural and urban suicide rates. This suggests a need for rural-specific suicide prevention efforts, especially aimed at the male rural population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 26 publications
9
60
2
2
Order By: Relevance
“…The results of the current study in relation to age and gender distribution are consistent with the findings in other countries 5,11,12,13,14 . In Spain, from 1986 to 2002, the suicide ratio between men and women was 3.4, and the oldest age group showed the highest rates 11 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the current study in relation to age and gender distribution are consistent with the findings in other countries 5,11,12,13,14 . In Spain, from 1986 to 2002, the suicide ratio between men and women was 3.4, and the oldest age group showed the highest rates 11 .…”
Section: Discussionsupporting
confidence: 92%
“…In Mexico, during the year 2001, the suicide rate was 3.72 per 100 thousand inhabitants, and was higher in men (6.14) than in women (1.32), and higher in the over-65 age group 16 . In Latin America, besides Brazil, an increase in suicide rates has been observed in recent years in Chile, Colombia, Paraguay, and The mean suicide rate from 1980 to 2005, as described in the current study (4.12 deaths per 100 thousand inhabitants), was lower than the mean for 53 countries with complete data available, which showed an aggregate and standardized rate of 15.1 deaths per 100 thousand inhabitants 6 , and was also lower than the rate of 17.6/100 thousand inhabitants in Japan from 1995 to 1997 12 .…”
Section: Discussioncontrasting
confidence: 49%
“…Studies from a number of different cultural contexts report that those living in rural areas are more at risk of suicide than those living in urban areas (Dudley, Kelk, Florio, Howard, & Waters, 1998;Gartner, Farewell, Roach, & Dunstan, 2011;Hempstead, 2006;Kapusta et al, 2008;Kim, Jung-Choi, Jun, & Kawachi, 2010;Phillips, 2009;Singh & Siahpush, 2002;Yip, Callanan, & Yuen, 2000). For example, research in Australia and New Zealand suggests that younger and older males in rural areas have higher suicide rates than their metropolitan counterparts (Caldwell, Jorm, & Dear, 2004;Dudley et al, 1998;Morrell et al, 1999;Yip et al, 2000), while older adults and females are reported as being more "at risk" in rural areas of Asia (Liu, Tein, Zhao, & Sandler, 2005;Phillips, Li, & Zhang, 2002;Pritchard, 1996;Yip et al, 2000).…”
Section: Rural Locations (N = 26)mentioning
confidence: 99%
“…Other researchers focus on the role of cultural norms in rural and urban areas, and the importance of values and relationships in the surrounding psycho-social environment (Alston, 2010;Baller & Richardson, 2002;Dudley et al, 1998;Hirsch, 2006;Pritchard, 1996). The relationship between rural residence and suicide has also been found to be sensitive to societal change, as studies have reported changes in the rural-urban suicide ratio over time (Chang, Gunnell, Wheeler, Yip, & Sterne, 2010;Kapusta et al, 2008;Page, Morrell, Taylor, Dudley, & Carter, 2007;Pearce, Barnett, & Jones, 2007). Durkheim's (1897) research investigated the influence of modernisation (conceptualised as the process of industrialisation, urbanisation and secularisation) on suicide rates in European nations in the late 1800s.…”
Section: Rural Locations (N = 26)mentioning
confidence: 99%
“…38 In a recent review of the literature from 1966 to 2006, the Hirsch 39 concluded that in many cases the suicide rates in rural areas is higher than in urban areas, and that rural communities present particular geographical, cultural, and socioeconomic characteristics, which possibly increase the risk of suicide. The 1970s in the US, suicide rates were lower in rural areas, while this was reversed in the 1990s and rural indicators in the last twenty years is higher (17.9/100,000) than in urban areas (14.9/100,000).…”
Section: Urbanization Of Residencementioning
confidence: 99%